Impacts of Climate Change on the People's Republic of China's Grain Output - Regional and Crop Perspective - Tun Lin; Guanghua Wan; Xian Xin; Yongsheng Zhang; Xiaoyun Liu (Asian Development Bank (ADB), 2011)
This paper investigates the impacts of climate change on the People's Republic of China's (PRC) grain output using rural household survey data. We highlight the regional differences of impacts by estimating output elasticities for different grain crops and different regions. Our results indicate that the overall negative climate impacts on the PRC's grain output range from –0.31% to –2.69% in 2030, and from –1.93% to –3.07% in 2050, under different emission scenarios. The impacts, however, differ substantially for different grain crops and different regions. From the perspective of grain crops, for example, modeling results suggest a decrease in rice output by 15.62%–24.26% in 2030 and by 25.95%–45.09% in 2050. Conversely, positive impacts of climate change are reported for both corn and soybean, with corn output increasing by 18.59%–24.27% in 2030 and 32.77%– 49.58% in 2050, and soybean output increasing by 0.48%–5.53% in 2030 and 3.96%–6.48% in 2050. The impacts on wheat output are relatively small. Looking at the regional perspective, modeling results reveal that the impacts of climate change in the northern and central regions of the PRC are positive. Specifically, climate change in Northern PRC is calculated to increase the country's grain output by 2.85%–4.80% in 2030, and 5.30%–8.49% in 2050; while in Central PRC the increases will be 3.53%–4.97% in 2030, and 8.91%–13.43% in 2050. Climate change in South PRC and Northwest PRC is projected to have small positive impacts on the country's grain output. On the other hand, the impacts of climate change are negative in the remaining regions, with reductions in 2030 of 4.10%–8.58% in East PRC, 2.29%–4.05% in Southwest PRC, and 2.58%–2.66% in Northeast PRC.
hdl:11540/2051
Keywords: 330; Getreide; Agrarproduktion; Klimawandel; China